TIPOLOGI MULTIAKAD DALAM PRODUK FATWA DEWAN SYARIAH NASIONAL-MAJELIS ULAMA INDONESIA PERSPEKTIF TEORI DAN BATASAN MULTIAKAD AL ‘IMRANI - Arfan, Abbas (ULUL ALBAB Jurnal Studi Islam, 2017)
Multi-contract theory or hibryd contracts (al ‘uqud al murakkabah) is one of the new theory in contemporary Islamic jurisprudence and among academicians who did a study about the multi-contract in fiqh perspective is Abdullah bin Muhammad bin Abdullah al ‘Imrani. Some fatwa products of NSB-IUC also used this multi-contract theory. This research type is qualitative with descriptive-qualitative and descriptive-quantitative method, the retrieval data technique with a literature review to research multi-contract typology in NSB-IUC fatwas perspective al ‘Imrani multi-contract theory and its limits. The conclutions of this research are: (1) among five typology multi-contract perspectives al ‘Imrani multi-contract theory only found two kinds of multi-contract in NSB-IUC’s fatwas, which are first; mutaqabilah (totalled by 7 or 31.8%) and second; mujtami’ah (totalled bt 15 or 68.2%), while third (mutanafiyah), fourth (mukhtalifah), and fifth (mutajanisah) each of them are 0, which means no (0%) multi-contract with those three typologies; (2) as for multi-contract typology in NSB-IUC’s fatwas, it is al ‘Imrani multi-contract perspective limits which means all multi-contract does not contradict al ‘Imrani multi-contract limits, therefore it is allowed by Sharia, but there are some alternative multi-contract in fatwa products wich kind of doubtful (syubhat), moreover it could lead us to riba, like Pembiayaan Rekening Koran Syariah (PRKS) transaction especially in two multi-contract options, which are: wakalah-murabahah and wakalah-qardh.